Ghanaian radiographers experience and commitment to the mandatory reporting law regarding suspected child physical abuse. Issue 1 (January 2023) - Antwi, W.K.; Aziato, L.
Abstract: Introduction: The best interests of the child shall be paramount in any matter concerning a child and it should be the primary consideration by any court, person, institution, or other body in any matter concerned with a child. This study sought to explore the influence of legislation on and professional commitment of radiographers towards suspected child physical abuse. Method: A semi-structured interview was conducted with 20 radiographers selected across all the regions in Ghana. The interviews were conducted exclusively by the first author with radiographers who reporting having experience of handling suspected child physical abuse cases. There were 14 male respondents with an age range of 30–54 years and six females aged from 25 to 57 years. Upon attaining data saturation, the thematically analysed data was managed using NVivo10 software. Results: Findings from the study showed that the legal framework for mandatory reporting of suspected child physical abuse was not known by radiographers. A lack of professional commitment to report cases of suspected child physical abuse was also identified. Themes that emerged from the study formed the basis of the discussion. Conclusion: This study revealed that radiographers interviewed were not well acquainted with national legislation requiring mandatory reporting. There is the urgent need to train radiographers on the laws protecting children to enhance their commitment to the reporting of suspected child physical abuse. Implication for practice: The understanding of the legal framework under which radiographers operate is imperative when considering obligations to report suspicious injuries among children.